Sgr A* near-infrared flares from reconnection events in a magnetically arrested disc. Issue 4 (11th August 2020) - Dexter, J; Tchekhovskoy, A; Jiménez-Rosales, A; Ressler, S M; Bauböck, M; Dallilar, Y; de Zeeuw, P T; Eisenhauer, F; von Fellenberg, S; Gao, F; Genzel, R; Gillessen, S; et al.
ABSTRACT: Large-amplitude Sgr A* near-infrared (NIR) flares result from energy injection into electrons near the black hole event horizon. Astrometry data show continuous rotation of the emission region during bright flares, and corresponding rotation of the linear polarization angle. One broad class of physical flare models invokes magnetic reconnection. Here, we show that such a scenario can arise in a general relativistic magnetohydrodynamic simulation of a magnetically arrested disc. Saturation of magnetic flux triggers eruption events, where magnetically dominated plasma is expelled from near the horizon and forms a rotating, spiral structure. Dissipation occurs via reconnection at the interface of the magnetically dominated plasma and surrounding fluid. This dissipation is associated with large increases in NIR emission in models of Sgr A*, with durations and amplitudes consistent with the observed flares. Such events occur at roughly the time-scale to re-accumulate the magnetic flux from the inner accretion disc, ≃10 h for Sgr A*. We study NIR observables from one sample event to show that the emission morphology tracks the boundary of the magnetically dominated region. As the region rotates around the black hole, the NIR centroid and linear polarization angle both undergo continuous rotation, similar to the behaviour seen in Sgr A* flares.